Adsorption of phosphate by polyvinyl alcohol-iron (iii) – sodium alginate hydrogel beads - Puteh Yahaya, Noranalyza (2019)
Phosphate is regarded as one of important nutrient elements to support the growth of biological organisms in aquatic environment. However, the presence of excessive phosphate is often responsible for causing eutrophication problems in lakes, confined water bodies and coastal water. In this paper, Polymeric ion exchanger is very selective towards phosphate and chemically stable. Polyvinyl alcohol, (PVA) hydrogel beads with Iron ion on its cross-linking structure were prepared by chemical cross-linking in the mixed aqueous solution of saturated boric acid and FeCl3. The effects of different parameters such as initial concentration, mass of adsorbent, pH, contact time and temperature have been studied to understand adsorption behavior of the adsorbent under various conditions. It was found that the increasing of the mass of FeCl3 and cross-linking time, the adsorption capacity first increasing because there are large number of adsorption sites and then decreasing may be attributed to overlapping or aggregation of adsorption sites resulting in a decrease in total adsorbent surface area. From FTIR analysis, after adsorption, the new peak at 1044.33 cm-1 appeared showed the bending vibration of phosphate. EDX analysis showed the surface of beads became smooth and the characteristic signal of phosphate also appeared. It showed that phosphate was adsorbed onto PVA-Iron hydrogel beads. From BET analysis, the beads exhibited a type III adsorption isotherm and are macroporous solid with a very small surface area. To study the mechanism of adsorption process, the Lagergren pseudo-first order model, pseudo-second order kinetic model were examined. It was found that this adsorption fitted with pseudo-first order kinetic model. Furthermore, the adsorption equilibrium data fitted to the Langmuir adsorption isotherm model indicating the adsorption was the homogeneous nature of the monolayer adsorption. The optimum condition of adsorption were occurred at pH 5, initial concentration of phosphate solution was 30 ppm and the mass of adsorbent used was 2.0g at room temperature. The maximum phosphate adsorption capacity of PVA hydrogel at this condition reached at 3.86 mg/g.